Nurse‐led follow‐up in survivorship care of gynaecological malignancies—A randomised controlled trial. (5th September 2020) - Ngu, Siew‐Fei; Wei, Na; Li, Justin; Chu, Mandy M. Y.; Tse, Ka Yu; Ngan, Hextan Y. S.; Chan, Karen K. L.
Abstract: Objective: To assess clinical and psychosocial outcomes of nurse‐led follow‐up in survivorship care of gynaecological malignancies. Methods: Women with endometrial or ovarian cancer who were attending regular post‐treatment follow‐up at a tertiary referral centre were randomised into two groups—group‐1: telephone follow‐up by nurses and group‐2: gynaecologists‐led clinic follow‐up. Women in group‐1 were asked about their symptoms and quality of life (QoL) by nurses. Women in group‐2 were followed up by gynaecologists and underwent symptom reviews and physical examinations. All ovarian cancer patients in both groups also had CA125 measured. All recruited women completed a QoL questionnaire (EORTC QLQ‐C30), HADS‐anxiety questionnaire and symptom checklist. Results: 385 women (215 with endometrial and 170 with ovarian cancer) were randomised. There was no significant difference in the detection of recurrence according to the two follow‐up protocols. However, women in the nurse‐led arm scored higher on emotional ( p  = 0.023) and cognitive functioning ( p  = 0.012). Those in the gynaecologist‐led arm scored higher on the HADS‐anxiety scale ( p  = 0.001) and were more likely to report symptoms. Conclusions: Our results demonstrate a preliminary non‐inferiority of nurse‐led follow‐up, with improved psychological morbidity and QoL. Thus, nurse‐led follow‐up can be considered an effective substitute for hospital‐based care.